Must China’s state enterprises follow the path of western governance to thrive? - Cheong, K.C.; Li, R.; Tan, E.C.; Zhang, M. (2011)
The prevailing discourse on the Chinese state and state enterprises is colored by equating these institutions with their Western counterparts. This had prevented a balanced assessment of their role and led to flawed policy prescriptions. Recognizing the historic and cultural context of these institutions would lead not only to better appreciation of their role but also to the conclusion that convergence to Western models and norms of governance is far from inevitable.